A framework to assess structural integrity of ageing offshore jacket structures for life extension. (November 2017) - Aeran, Ashish; Siriwardane, Sudath C.; Mikkelsen, Ove; Langen, Ivar
Abstract: The structural integrity assessment of ageing structures for possible life extension has been identified as a growing challenge in the oil and gas industry worldwide. Although the available guidelines provide a general assessment process, it is necessary to have more detailed guidelines. This can be achieved by adding relevant theories and models which can capture time-dependent structural degradation more precisely. To address this, a new framework for possible life extension is proposed in this paper. The proposed framework provides more precise corrosion models, new damage theories and assessment guidelines to predict the remaining fatigue life and check the structural adequacy in all the limit states during the whole extended service life. Initially, the paper presents the proposed framework in detail. The framework approach is then applied to an ageing jacket as a case study and results are compared with conventional approach. The proposed approach results in a remaining life of ten years as compared to one year using the conventional approach. Thus, the jacket structure can be safely operated for an additional nine years using the proposed approach. Recommendations are also made on increasing the remaining fatigue life using life improvement techniques. Finally, the applicability, significance and validity of the proposed framework are discussed. Highlights: A novel framework to assess structural integrity of ageing offshore jacket structures is proposed. Provides recommendations for simulating structural degradation, loading history and fatigue strength for corroded details. Effect of localized corrosion on SCF's, new fatigue damage theory and guidelines for strengthening/inspection are included. Applicability, significance and validity of the framework are highlighted through a case study on an aged jacket structure.